Efeitos da separação materna na área imunopositiva para astrócitos no hipocampo de ratos jovens - SILVA, Cristiana Pires da (2022)
Introduction: Glial cells compose most of the cells in nervous system, among which are highlighted astrocytes. Astrocytes have many functions in the central nervous system (CNS), among which are structural, vascular, neuronal survival and synaptic plasticity functions, also having a fundamental role in regulating the transmission of information in the nervous system and being the main source of growth factors for neurons, these cells can be identified by the expression of glial fibrillary acidic protein (GFAP). The development of the human brain, from the first stages of intrauterine life to adult life, happens gradually and the effects of early experiences impact is related to the individual's ability to respond and adapt to environmental stimuli. Experiences characterized as stressful ones have a negative influence on brain development and can compromise the subject’s health, while environments enriched with stimuli induce healthy development. In this regard, stressful neonatal events such as maternal separation (MS), can promote structural changes in the nervous system and increase the predisposition to psychiatric diseases. Studies suggest that chronic stress can cause hippocampal changes, impacting the reduction in volume, number of neuronal and glial cells and in synaptic transmission as well. Objective: To study if young animals (21 days) submitted to neonatal MS have changes in the immunopositive area for astrocytes in the hippocampal cortex. Methodology: This study is a descriptive experimental research with a quantitative approach. The research was divided into three phases: 1) behavioral experiments: concerns the maternal separation procedure; 2) morphological experiments: in which the brains were pinned, frozen, sectioned and placed on slides, then their sections were subjected to the immunofluorescence procedure for the GFAP protein to mark the immunopositive area for astrocytes; 3) stereological quantification: in order to quantify the immunopositive area and the percentage marked for GFAP in specific regions of the dentate gyrus, such as in the granular and molecular layers, and hippocampus hilum of young animals. Results: No significant changes were observed in relation to a positive area and GFAP between animals at separation and controls in the granular, molecular and hippocampal layers. Houve redução no volume da camada granular do giro denteado do hipocampo nos animais submetidos à separação materna. Em relação ao volume das camadas molecular e hilo não foram observadas diferenças significativas. There was a significant reduction in the volume of the granular layer of the dentate gyrus of the hippocampus in animals submitted to maternal separation. Regarding the volume of molecular layers and hilum, no differences were observed.